Perilaku Berbahasa Indonesia Sebagai Cermin Budaya di Era Global (Bahasa Gaul di SMP) - Novita Trianto Hasibuan (Balai Bahasa Sumatera Utara, 2019)
Slang is a sign that the Indonesian development among young people is very bad, because they slang also can not be regarded as the standard language and not in accordance with the EYD. A shift Indonesian writing and pronunciation is due to the emergence of a new language among teenagers that makes them more confident when they use the new language which they refer to as slang. Teens today are more likely to use slang that would erode kebakuan owned Indonesian. The purpose of this study is to analyze and identify the mistakes of students' language, in terms of phonology and morphology. In this discussion the authors focus more on assessing the level of phonology. Based on the findings of researchers at the number of errors bebrbahasa, both in vocal phonemes Changes, Additions phoneme consonant, vowel phonemes Disappearance, Disappearance double vowel phonemes into a single vowel, etc.